Thermophilic dentrification of high-nitrate industrial wastewater - Lim, Jose Marie Uy
Thermophilic high-nitrate denitrification was investigated using a specific industrial wastewater with 14,000 mg/l of NO3-N. The wastewater has a soluble COD of 110,000 mg/l, 75 to 85% of which was found to be ethylene glycol. The wastewater contains no ammonia or nitrite, making nitrate as the N-source for bacterial cell synthesis. A CSTR set-up was used for batch and continuous thermophilic denitrification. Biomass yield on the electron donor (ethylene glycol) and electron acceptor (nitrate) was found to be 80 to 85% lower when compared to results of mesophilic denitrification. A pure strain of Bacillus stearothermophilus, a known thermophilic denitrifier was found to accelelrate denitrification removal rates. The wastewater was supplemented with magnesium sulfate, sodium biophosphate, and Vishniac solution (combination of metals and other micro-nutrients). The optimum temperature is 62°C. Complete denitrification can be expected between 56°C up to 62°C without significant nitrite accumulation. As temperature increases beyond this optimum temperature, the % nitrate removal rate decreases up to a low value of 10% at 75°C.